Glocalizing Inclusive Quality Education in Hong Kong: From Pedagogical Challenges to Research Opportunities - Li, Eddy (Frontiers in Education, 2018)
Since the launch of the Whole School Approach to Integrated Education in 1997, mainstream schools in Hong Kong have been admitting an increasing diversity of learners. They include, for example, children identified with different categorical learning needs, and more recently those who learn Chinese as a second language. Nonetheless, many teachers in this predominantly Chinese community remain sceptical to date about their pedagogical capacity for achieving greater inclusion. This paper discusses the contextual challenges of glocalising inclusive quality education in Hong Kong. In response to the teachers’ concern about their professional readiness to support the learning of all children, it proposes a research framework for understanding their inclusive pedagogy – as a bottom-up approach to inform the development of more cultural-specific inclusive teacher education therein.